Spatiotemporal variability of magmatic products under a changing structural and tectonic context: a case study in the Andes of southern Central Chile - Piquer, José; Fischer, Tomás; Torres, Francisco; Plissart, Gaëlle (Frontiers in Earth Science, 2023)
In a subduction setting, the type of magmatic products which reach the upper crust, and eventually the surface, depends on several variables, among which some of the most relevant are the tectonic regime, and the orientation of magma pathways relative to the predominant stress tensor. To better understand this relationship, we studied in detail an area of the Andes of southern Central Chile in which subduction-related magmatism has been active at least during the last 18 m.y. The relationship between high-angle faults and magmatism was studied, and the spatiotemporal variations on the stress tensor were analyzed. The chemistry of the different magmatic products was used to evaluate the magma “fertility”, understood as its potential to form a giant porphyry-type deposit. The age of the studied units is constrained by new U-Pb zircon ages, complemented with previous geochronological studies. Three main high-angle fault systems are present: ~NW striking structures control the emplacement of plutonic bodies, while ~NE – ENE and N – NNE faults, more parallel to the prevailing orientation of σ1 since the middle Miocene, control the emplacement of dike swarms and volcanic alignments. Regarding the geochemical characterization, a transition towards steeper REE patterns and higher fertility indices is observed in the earliest facies of the La Invernada Plutonic Complex (~15-14 Ma), coincident with a middle Miocene orogenic event described at this latitude by previous authors. The Pliocene La Resolana intrusions show higher magma fertility indices; however, they are still considerably lower than those typical for porphyry-forming magmas in the same Andean region. It is concluded that the contrasting fertility observed in coeval intrusions emplaced under the same tectonic context, cannot be explained by continental-scale processes; instead, they are related to differences in the local pathways of magma ascent through the crust. Fault systems which are miss-oriented relative to the predominant orientation of σ1 appear to favor longer magma residence times, achieving a higher degree of differentiation and fertility in most cases crystalizing within the upper crust, while magmas ascending through more favorably oriented faults are more primitive, and often reach the surface forming stratovolcanoes and alignments of monogenetic vents.